The Relationship Between Clinical And Anthropometric Factors And Diabetic Neuropathy In Type 2 Diabetes Mellitus Patients At Primary Healthcare Facilities - Maria Karolina Selano; Emirensiana Anu Nono; Kristiana Prasetia Handayani; Maria Dolorosa Peni Sogen; Gregorius Tsiompah (Journal of Nursing Management Innovations, 2026)
Background: Diabetic neuropathy is a chronic complication commonly occurring in type 2 diabetes mellitus patients and serves as the primary cause of foot ulcers and amputations. In primary healthcare facilities, early detection of neuropathy faces limitations in resources and diagnostic tools. Therefore, identifying easily measurable clinical and anthropometric factors is crucial to support initial screening in at-risk populations. Aims and Scope of the Paper: This study aims to analyze the relationship between clinical factors and anthropometric parameters with the incidence of diabetic neuropathy in patients with type 2 diabetes mellitus at primary healthcare facilities. The scope of the study includes the evaluation of variables such as age, gender, duration of diabetes, random blood glucose levels, blood pressure, and body mass index (BMI). Methods: This study employed an analytic observational design with a cross-sectional approach. A total of 120 patients with type 2 diabetes mellitus were recruited using purposive sampling. Diabetic neuropathy was assessed using the monofilament test. Independent variables included body mass index (BMI), duration of diabetes, and hypertension status. Data analysis was performed using the chi-square test with calculation of prevalence ratios (PRs) and 95% confidence intervals (CIs). Results: Of the 120 respondents, 78 (65.0%) were diagnosed with diabetic neuropathy. Overweight/obese BMI was significantly associated with neuropathy (PR = 4.39; 95% CI: 2.17–8.89; p < 0.001). Diabetes duration of more than 5 years also demonstrated a significant association (PR = 2.27; 95% CI: 1.35–3.83; p = 0.002). Hypertension was significantly associated with diabetic neuropathy (PR = 2.91; 95% CI: 1.58–5.36; p < 0.001). Conclusion: Overweight/obese BMI, longer duration of diabetes, and hypertension were significantly associated with diabetic neuropathy in patients with type 2 diabetes mellitus at primary healthcare facilities. These simple clinical and anthropometric parameters can be utilized as a basis for risk screening in the early detection of diabetic neuropathy in primary care settings.